A pathogenesis related protein, VpPR-10.1, from Vitis pseudoreticulata: an insight of its mode of antifungal activity. - Teng-Fei Xu; Xiao-Chen Zhao; Yun-Tong Jiao; Jin-Yu Wei; Lan Wang; Yan Xu (PLoS ONE)
Previously, VpPR-10.1 was isolated and characterized from a cDNA library of a fungus-resistant accession of Chinese wild grape (Vitis pseudoreticulata). We found that expression of VpPR-10.1 is affected by the fungal pathogen Erysiphe necator. To investigate the biochemical basis of the nuclease activity of VpPR-10.1 and its role in antifungal resistance, we generated recombinant VpPR-10.1 as well as site-directed mutations targeting three conserved amino acid residues among plant PR-10 s: Lys55, Glu149, and Tyr151. We showed that wild-type recombinant VpPR-10.1 exhibits both RNase and DNase activities. Mutant VpPR10.1-Y151H essentially retained all these activities. In contrast, VpPR10.1-K55N, where Lys55 in the P-loop region is mutated to Asn, and VpPR10.1-E149G, where Glu149 is mutated to Gly, lost their nuclease activity, indicating that both residues play a critical role in catalyzing RNA and DNA degradation. Furthermore, VpPR10.1 and VpPR10.1-Y151H inhibited the growth of the cultured fungal pathogen Alternaria alternate. Through transient expression in grapevine, we also demonstrated that VpPR10.1-K55N and VpPR10.1-E149G compromised resistance to E. necator. Finally, we further found that VpPR-10.1 can lead to programmed cell death and DNA degradation when incubated with tobacco BY-2 suspension cells. We show here that Lys55 and Glu149, but not Tyr151, are required for the RNase, DNase and antifungal activities of VpPR-10.1. The strong correlation between the level of VpPR-10.1 nuclease activity and its antifungal property indicates that the former is the biochemical basis for the latter. Taken together, our experiments revealed that VpPR-10.1 is critical in mediating fungal resistance in grape, potentially playing a dual role by degrading pathogen RNA and inducing programmed death of host cells.